One of the work accidents in the military unit: food poisoning and solution recommendations - Karadağ, Turabi; Dayıoglu, Habip (Progress in Nutrition, 2021)
Food poisoning is one of the common diseases that affect public health a lot. There is a high risk of food poisoning in military units, as in all places where mass nutrition is provided. Food poisoning is an infection or intoxication caused by consumption of food. Although food poisoning usually causes mild and short-term discomfort, it can sometimes be seen seriously, with fatal consequences. In this study, food poisoning, which is one of the occupational accidents in military units, was examined. Especially in recent years, food poisoning has been experienced seriously in military units, many military personnel get sick and even martyrs are given. As a result of the research, it was revealed that food poisoning cases were experienced in 17 military units and 1499 military personnel were affected and unfortunately 1 soldier was martyred. In this study, safety precautions to be taken to prevent and minimize food poisoning experienced in military units and health conditions to be provided are discussed in detail within the framework of occupational safety and worker health.